The secret lives of murderers' wives - Arnott, Elizabeth (Berkley, 2026)
"A remarkable trio whose lives were cracked wide open by their husbands' crimes unite to catch a serial killer in this dazzlingly captivating novel. Beverley, Elsie, and Margot are not your average housewives. They are all wives of convicted serial killers. In sun-drenched California during the summer of 1966, the three women form an unlikely friendship after the discoveries of their husbands' brutal crimes. With their exes-some of California's most infamous convicted serial killers-dead or behind bars, they are attempting to forge a new future for themselves. Headstrong Beverley compulsively tries to maintain control of everything around her, all the while raising two children. Bookish Elsie fights day in and day out for the chance to make a name for herself in the newsroom, working around the men who sneer at her journalistic career goals. Glamorous Margot refuses to take anything seriously and devotes all her energy toward maintaining appearances that everything is fine-anything to quell her shame that her husband deceived her. They know people look at them and think only one thing: how could they not have known, when their husbands were right under their noses, committing horrific crimes? How much guilt is theirs to carry? And yet, when a string of killings hits the news, the three women-underestimated, overlooked, shrewd-decide to get to work. After all, who better to catch a killer than those who have shared their lives and homes with one? At once a riveting portrayal of shattered trust and a story of gripping suspense, The Secret Lives of Murderers' Wives is a testament to the intricacies of women's lives and how the deep bonds of female friendship can empower, uplift, and lead us to endure"-- Provided by publisher.